Evaluasi dan Mitigasi Distorsi Harmonisa Transformator 1250 kVA Beban Motor Pompa Air - Anang Dasa Novfowan; Mochammad Mieftah; Dhimas Dhesah Kharisma (Elposys: Jurnal Sistem Kelistrikan, 2025)
As a fundamental part of modern life, electricity must be both reliable and efficient—qualities that can be affected by issues like voltage unbalance and harmonic distortion. This study investigates power quality in a 1250 kVA transformer that supplies continuous power to water pump motors at PDAM Wendit, which operate 24 hours a day. Data were collected using the Power Logic PM5100, while a passive filter design was developed and tested through simulations in Matlab/Simulink.The results show a Voltage Unbalance Factor (VUF) of 0,32%, which falls within the acceptable range according to NEMA standards. However, the Total Harmonic Distortion of Voltage (THDV) was found to be between 8% and 9,2%, exceeding the 8% limit recommended by IEEE 519-2014. The average power factor measured was 0,9. To address the excessive harmonic distortion, a single-tuned passive filter was designed targeting the dominant third-order harmonics. Simulations revealed that the filter successfully lowered the THDV to below 6% and reduced current by 1,5% to 3,4%. These findings highlight the importance of harmonic mitigation not only in meeting regulatory standards but also in improving energy efficiency, reducing power losses, and ensuring longer operational life for critical equipment like water pump motors.